PENGARUH LINGKUNGAN KERJA NON FISIK DAN WORK FAMILY CONFLICT TERHADAP KINERJA MASINIS UPT CREW KERETA API SURABAYA KOTA - ANUGRAHRIA LILIK LUKRISNYAWANTOK, CORNELIUS (Jurnal Ilmu Manajemen (JIM), 2016)
UPT Train Crew Surabaya City is part of the company PT. Kereta Api Indonesia (KAI) Regional Operations 8 Surabaya are engaged in services. The company has a goal to become a services based company that excels in global competition, these objectives can be achieved if the machinist excellent performance in the face of global competition. The companys success in managing performance is largely determined by non physical work environment and work family conflict. If the working environment of non physical, the better the performance of the machinist will get better. On the contrary if it appears work family conflict, then this will cause the pressure that led to the decline in the performance of the machinist. This study aims to examine and analyze the influence of the working environment of non physical and work family conflict on the performance of the machinist. This study is causally using a quantitative approach. The sampling technique using saturated sample number of 67 respondents. The statistical analysis used is multiple linear regression. The results of this study explains that the non physical work environment positive and significant effect on the performance of the machinist. There is no influence work family on machinist performance. Simultaneously, non physical work environment and work family conflict affect the performance of the machinist.